Levels of Human Immunodeficiency Virus DNA Are Determined Before ART Initiation and Linked to CD8 T-Cell Activation and Memory Expansion. (28th November 2019) - Martin, Genevieve E; Pace, Matthew; Shearer, Freya M; Zilber, Eva; Hurst, Jacob; Meyerowitz, Jodi; Thornhill, John P; Lwanga, Julianne; Brown, Helen; Robinson, Nicola; Hopkins, Emily; Olejniczak, Natalia; et al.
Abstract: Initiation of antiretroviral therapy (ART) in early compared with chronic human immunodeficiency virus (HIV) infection is associated with a smaller HIV reservoir. This longitudinal analysis of 60 individuals who began ART during primary HIV infection (PHI) investigates which pre- and posttherapy factors best predict HIV DNA levels (a correlate of reservoir size) after treatment initiation during PHI. The best predictor of HIV DNA at 1 year was pre-ART HIV DNA, which was in turn significantly associated with CD8 memory T-cell differentiation (effector memory, naive, and T-bet − Eomes − subsets), CD8 T-cell activation (CD38 expression) and T-cell immunoglobulin and mucin-domain containing-3 (Tim-3) expression on memory T cells. No associations were found for any immunological variables after 1 year of ART. Levels of HIV DNA are determined around the time of ART initiation in individuals treated during PHI. CD8 T-cell activation and memory expansion are linked to HIV DNA levels, suggesting the importance of the initial host-viral interplay in eventual reservoir size. Abstract : Human immunodeficiency virus (HIV) DNA persists within the viral reservoir despite therapy. A longitudinal analysis of 60 individuals treated during early HIV infection showed that HIV DNA levels are "set" early in infection and predicted by an activated immune response.